The Study on Relationship between Tourism Revenues and Economic Growthin Lao PDR - SOUKAVONG, Bounthone; KYOPHILAVONG, Phouphet; SENGCHAN, Souksamone; LATTANAKOSON , Sinnamone; LIENGSOUNON, Khamsao (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research aims to study the relationship between tourism revenues and economic growth in Lao PDR. The purpose of this research was to study the overall economic growth and tourism revenues in Lao PDR during the 1991-2018 period and investigate the causality of tourism revenues and economic growth in Laos by using an econometric model called the ARDL model to analyze time-series data from 1991 to 2018. Moreover, EViews 10 is also included as a tool of analysis technics. The results of this study found that economic growth is gradually growing at an average of 7%. The services sector is expanding, accounting for 41.62% of GDP in 2018, with an average annual growth rate of 7.57% from 1991 to 2018. to 2018. While annual tourism revenue increased by 30 percent on average, particularly in 2018, the Lao government began the year by generating tourism revenue of up to 811 million US dollars.The Co-Integration test shows that the level of statistical correlation; whenever a 1% increase in the gross domestic product, in the long run, tends to increase tourism revenue by 3.81% and if tourism revenue increases by 1%, it will result in an increase in the gross domestic product of 0.24%. The case of short-term estimates (ECM) shows that if tourism revenue D(RTR) changes by 1%, gross domestic product (GDP) changes by 0.43% in the opposite direction, but there is no statistical significance. In the short term, changes in tourism revenues affect the change in gross domestic product,meaning that in the short-term when tourism revenue increases, it will increase gross domestic product. Which is in accordance with assumptions that. Finally, the Granger Causality Test between the two variables found that: ln_RTR tourism revenue caused a change in gross domestic product with 99% significance levels, while GDP did not cause a change in RTR.